2020
DOI: 10.3389/fphar.2020.565090
|View full text |Cite
|
Sign up to set email alerts
|

Ethyl Acetate Extract of Selaginella doederleinii Hieron Induces Cell Autophagic Death and Apoptosis in Colorectal Cancer via PI3K-Akt-mTOR and AMPKα-Signaling Pathways

Abstract: Colorectal cancer is one type of cancer with high incidence rate and high mortality worldwide. Thus, developing new chemotherapeutic drugs is important. The Selaginella doederleinii Hieron ethyl acetate (SDEA) extract showed good anti-colon cancer effect in vitro and in vivo, but its mechanism is unclear. This study aimed to further reveal the anticolon cancer effect of SDEA and its possible mechanism. The effects on cell viability, apoptosis, autophagy, and cell cycle in colorectal cells (HT29 and HCT116) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 26 publications
1
29
0
Order By: Relevance
“…Future preclinical and clinical studies must be carried out [ 162 ]. The study conducted by Li S et al evaluated the effect of the extract Selaginella doederleinii Hieron ethyl acetate (SDEA) in vitro and in vivo [ 178 ]. Using HT29 and HCT116 cell lines, the anti-tumoral effect of SDEA was manifested by cell morphological changes, cell cycle arrest, autophagy, and apoptosis [ 178 ].…”
Section: Pi3k/akt/mtor and Mapk Signaling Pathways Inhibitorsmentioning
confidence: 99%
See 3 more Smart Citations
“…Future preclinical and clinical studies must be carried out [ 162 ]. The study conducted by Li S et al evaluated the effect of the extract Selaginella doederleinii Hieron ethyl acetate (SDEA) in vitro and in vivo [ 178 ]. Using HT29 and HCT116 cell lines, the anti-tumoral effect of SDEA was manifested by cell morphological changes, cell cycle arrest, autophagy, and apoptosis [ 178 ].…”
Section: Pi3k/akt/mtor and Mapk Signaling Pathways Inhibitorsmentioning
confidence: 99%
“…The study conducted by Li S et al evaluated the effect of the extract Selaginella doederleinii Hieron ethyl acetate (SDEA) in vitro and in vivo [ 178 ]. Using HT29 and HCT116 cell lines, the anti-tumoral effect of SDEA was manifested by cell morphological changes, cell cycle arrest, autophagy, and apoptosis [ 178 ]. Moreover, the SDEA extract may induce the loss of the mitochondrial membrane potential, increases the autophagic flux, and will inhibit the PI3K/AKT/mTOR signaling pathways [ 178 ].…”
Section: Pi3k/akt/mtor and Mapk Signaling Pathways Inhibitorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Delicaflavone (DF), a rarely occurring biflavonoid, is an active ingredient isolated from Selaginella doederleinii Hieron, a traditional Chinese medicine used for health promotion and treatment of various cancers ( Liu et al, 2011 ; Li et al, 2020 ). Modern pharmacological studies have demonstrated that DF induces reactive oxygen species (ROS)-mediated apoptosis and cell cycle arrest via the PI3K/AKT/mTOR and Ras/MEK/Erk signaling pathways, which results in autophagic cell death via the Akt/mTOR/p70S6K signaling pathway ( Sui et al, 2017 ; Yao et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%